PENYIMPANGAN PERILAKU TOKOH UTAMA DALAM NOVEL THE SWEET SINS KARYA RANGGAWIRIANTO PUTRA KAJIAN PSIKOLOGI SASTRA - Ngalong, Virgilius Pasifikus (Humanis; Volume 14. No.2. Pebruari 2016, 2016)
The research was about the analysis of The Sweet Sins (TTS) written by Rangga Wirianto Putra. Psycologcal approach which was focus on psycosexual was applied to analyze the novel. There were three problems analyzed: (1) novel structure, specifically the intrinsic elements and the relation between the elements in a unity of the sotry. (2) intertextual relation between TTS and the lyric of Dosa Termanis  by Tere. (3) Personality psychology aspect, specifically psychosexual of the two main characters of TTS. Theories applied in the research were theory of structure, intertextual theory, and psychological theory. The theory of structure was used to analyze the intrinsic elements and the relation between the elements. Intertextual theory was used to find the relation between the two literary texts. The psychological theory was applied to find the personality aspect and the psychosexual of the main character. Sigmun Freud’s psychological theory  which categorized the human personality into three mental aspects: id, ego, and superego, the psychosexual theory  of Elizabeth Hurlock and A. Supraktiknya, and some other theories were use to analyze the psychological aspects. The result of the researh showed that the intrinsic elemets of the novel had the homosexual theme. The theme was explained by the author in a solid naration in the strong relationship between the personality background of the characters. Psycoligical analysis showed that the novel was succesfully told the mental complexity of the main characters who were seriously involved in homosexual relationship. At the end of the story, there wer two messages implied: (1) homosexual could be in everyone and had to be avoided because it against the law and the social norms, specifically in Indonesia; (2) to teach the readers to read people from many different points of view.
Keywords: Personality psychology, psychosexual, TSS